2019
DOI: 10.1007/s00334-018-00711-4
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the late Holocene vegetation history of the East European forest-steppe: case study Sudzha (Kursk region, Russia)

Abstract: Today the East-European forest-steppe is an agricultural landscape with very few remains of the former natural vegetation. The history of the transformation from natural vegetation to a human-made landscape in the area of Sudzha (Kursk region, Russia) is studied here. Therefore, we compare the off-site pollen record Sudzha with three on-site pollen records obtained from the archaeological site Kurilovka-2. The sediment core Sudzha covering the last 2500 years was taken from an oxbow lake in an area with archae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The composition and structure of mid to late Holocene vegetation of the eastern Lower Danube Plain resembled, to a large degree, that of other European forest steppe areas, although particularities also exist. Whilst in central eastern European forest steppe, Quercus and Carpinus betulus were the dominant tree species with a lower occurrence of Tilia, Ulmus, Corylus and Pinus (Magyari et al, 2010;Feurdean et al, 2015;Kuneš et al, 2015), on the Eastern European Plain, Tilia and Quercus, and in some places Pinus, were the dominant tree taxa (Kremenetski et al, 1995;Novenko et al, 2016Novenko et al, , 2018Shumilovskikh et al, 2018Shumilovskikh et al, , 2019. Forests in the Black Sea region also included thermophilus taxa i.e., Quercus cerris, C. orientialis (this study, Marinova et al, 2006;Tonkov et al, 2014) Remarkably, Carpinus orientalis was found to be significantly more abundant around the Black Sea coast i.e., Romania (20%), Bulgaria (>5%), or with only scattered occurrences in Ukraine, whilst it was absent from Central European forest steppe.…”
Section: Comparison With Other European Forest Steppe Regionsmentioning
confidence: 99%
“…The composition and structure of mid to late Holocene vegetation of the eastern Lower Danube Plain resembled, to a large degree, that of other European forest steppe areas, although particularities also exist. Whilst in central eastern European forest steppe, Quercus and Carpinus betulus were the dominant tree species with a lower occurrence of Tilia, Ulmus, Corylus and Pinus (Magyari et al, 2010;Feurdean et al, 2015;Kuneš et al, 2015), on the Eastern European Plain, Tilia and Quercus, and in some places Pinus, were the dominant tree taxa (Kremenetski et al, 1995;Novenko et al, 2016Novenko et al, , 2018Shumilovskikh et al, 2018Shumilovskikh et al, , 2019. Forests in the Black Sea region also included thermophilus taxa i.e., Quercus cerris, C. orientialis (this study, Marinova et al, 2006;Tonkov et al, 2014) Remarkably, Carpinus orientalis was found to be significantly more abundant around the Black Sea coast i.e., Romania (20%), Bulgaria (>5%), or with only scattered occurrences in Ukraine, whilst it was absent from Central European forest steppe.…”
Section: Comparison With Other European Forest Steppe Regionsmentioning
confidence: 99%
“…There is clear evidence for such over-exploitation from a range of territories. Pollen data in the forest-steppe zone in the Eastern European Plain (Novenko et al, 2015(Novenko et al, , 2016Shumilovskikh et al, 2018Shumilovskikh et al, , 2019Lukanina et al, 2022) demonstrate that the first destructions of the forests occurred in the Iron Age, leading to total deforestation for agriculture in many areas within the last 300-500 years. Eastern Mediterranean records from Turkey point to similar developments (van Zeist and Bottema, 1991;Shumilovskikh et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%